Provision of Public Goods and Services by The Government and Property Tax Compliance - Baiq Syaifa Noor Ilmiyani; Sartika Djamaluddin Djamaluddin (Journal of Indonesian Applied Economics, 2020)
The compliance of tax payments can be seen from the concept of reciprocity between the government as the tax collector in providing public goods and services to the public as taxpayers. The objective of this research is to know the relationship between provision of public good by government, such as quality of schools, public health center (puskesmas), hospitals and roads with property tax (PBB-P2) compliance. Tobit estimation results show that there is a positive relationship between providing roads to PBB-P2 compliance. In addition, it also found that citizen education has a negative relationship toward PBB-P2 compliance and the performance of tax collectors has a positive relationship with PBB-P2 compliance. In this case, improving the quality of road provision also the performance of tax collectors can be a concern of the government as an effort to improve PBB-P2 compliance.